Pengaruh Service Quality Terhadap Student Satisfaction Taruna Poltekip Prodi Manajemen Pemasyarakatan Angkatan LV - Nikita RM Elyus; Padmono Wibowo (JOURNAL SAINS STUDENT RESEARCH, 2023)
Education is the most important factor in building human resources. However, considering the transition in the education environment that has led to an increase, it has created competition in improving the quality of services to achieve student satisfaction. This type of research uses quantitative research. The research data sources consist of primary data and secondary data. The data acquisition technique in this research involves distributing questionnaires, which are then processed using SPSS 27 software. Based on the results and discussion, it can be concluded that all the processed data are valid and reliable. In addition, the research data is normally distributed with a value of 0.200 > 0.05, and it has a homogeneous population. Furthermore, variables X and Y also have a linear relationship with a value of 0.021 > 0.05, and they have a correlation based on Pearson correlation, indicating that variables X and Y have a strong positive relationship with a value of 0.690 > 0.05. However, the influence of X on Y is only 47.6%, while 52.4% is influenced by other variables. Therefore, based on the research results, it can be concluded that Ho is rejected with a value of 0.000 < 0.005. This means that variable X significantly affects variable Y for the Cadets of Poltekip Prodi Manajemen Pemasyarakatan Angkatan 55. Additionally, a regression equation is obtained, which is Y = 8.846 + 0.123X..